AIRBORNE DISPERSION OF ASBESTOS FIBERS FROM SERPENTINITES: A SIMULATION ON OPHIOLITES OF PIEVESCOLA AREA (TUSCANY, ITALY) - Zaccagnini, Edoardo; Marroni, Michele (Ofioliti, 2013)
In Italy, the asbestos-related hazard is still high, mainly due to airborne dispersion of fibers as a consequence to quarrying activities into asbestos-bearing rocks, as serpentinites or basalts. The Ministerial Decree 14/05/1996 provides a method to define the hazard deriving from the exploitation of the asbestos- bearing rocks quarying, but the proposed procedures are unclear from a geologic point of view, and not so effective for a precise hazard assessment. In this paper, we present an integrated approach based on geological, mineralogical and petrographical standard investigations on serpentinites and we test a model of airborne dispersion of fibers in order to propose more effective procedures in order to assess the asbestos-related hazard. The adopted approach consists of 5 successive steps: 1) detailed structural mapping and collection of samples representative of the cropping out rocks, 2) petrographical study of selected thin sections of serpentinites with the aim to assess the presence of fibrous minerals, 3) X-Ray powder diffraction analyses for the identification of the species of fibrous minerals, 4) determination of the Index of Release according to the Ministerial Decree 14/05/1996 in order to deter- mine the amount of fibrous minerals released by crushing of the asbestos-bearing serpentinites and 5) modelling of the airborne dispersion of asbestos fibers by the quarrying activity based on the data collected in the previous steps. This approach has been simulated for an area located west of Pievescola, south of Casole d’Elsa (Southern Tuscany), where no quarrying activity occurs or is scheduled for the future. The implications of the adopted approach are also discussed in order to identify valuable procedures to minimize the asbestos-related hazard.